Diversity in the Enteric Viruses Detected in Outbreaks of Gastroenteritis from Mumbai, Western India - Renu Bhardwaj (International Journal of Environmental Research and Public Health, 2012)
Faecal specimens collected from two outbreaks of acute gastroenteritis that occurred in southern Mumbai, India in March and October, 2006 were tested for seven different enteric viruses. Among the 218 specimens tested, 95 (43.6%) were positive, 73 (76.8%) for a single virus and 22 (23.2%) for multiple viruses. Single viral infections in both, March and October showed predominance of enterovirus (EV, 33.3% and 40%) and rotavirus A (RVA, 33.3% and 25%). The other viruses detected in these months were norovirus (NoV, 12.1% and 10%), rotavirus B (RVB, 12.1% and 10%), enteric adenovirus (AdV, 6.1% and 7.5%), Aichivirus (AiV, 3% and 7.5%) and human astrovirus (HAstV, 3% and 0%). Mixed viral infections were largely represented by two viruses (84.6% and 88.9%), a small proportion showed presence of three (7.7% and 11%) and four (7.7% and 0%) viruses in the two outbreaks. Genotyping of the viruses revealed predominance of RVA G2P[4], RVB G2 (Indian Bangladeshi lineage), NoV GII.4, AdV-40, HAstV-8 and AiV B types. VP1/2A junction region based genotyping showed presence of 11 different serotypes of EVs. Although no virus was detected in the tested water samples, examination of both water and sewage pipelines in gastroenteritis affected localities indicated leakages and possibility of contamination of drinking water with sewage water. Coexistence of multiple enteric viruses during the two outbreaks of gastroenteritis emphasizes the need to expand such investigations to other parts of India.